The Story Description in poetry of Al- Aasha Al- Kabeer - عبد الله يونس الزبيدي, جنان (Journal of College of Education, 2020)
The description regards a literary technique for moving the reality from material image to linguistic image work to form the reciting elements for the character. Al- Aasha had distinguished with his novel style, had came his interesting with this kind of poetry.The research consist of introduction and three themes, the introduction came to limit concept of the novel description, the first theme specify for study (the character description), the second theme had came to study the (event description), the third theme came to study the (place description), and end with a conclusion.